Financial Statement System for Small Business - Mohd Saufi, Mohd Jazmi (Universiti Teknologi Petronas, 2006)
This project focuses on with the development of Financial Statement System for Small Businesses which apply to any small business in Malaysia. In this day and age where IT technologies permeate virtually every facet of society, business organizations especially small and medium companies should not miss the advantages of it. This research will look at the acceptance level and effectiveness of using financial management system among the small companies in Malaysia. The target is to find out the rationale behind these problems and solutions to make the development of financial management system successful. The research involves small businesses in Malaysia such as grocery stores, bakeries, computer shops, stationery shops and so on. In this project, several techniques are used to elicit information such as conducting interview session with businesses, carrying out surveys at the shops and also research on the Internet, journals and books. In this project, the requirements for the system are listed and ranked. Based on the requirements, the prototype of Financial Statement System for Small Business will be developed to ensure that it satisfies all the requirements. Based on the findings that have been done, it highlights that the industry should realize the potential that Financial Statement System for Small Businesses offers and its ability to help the small and medium companies to compete in larger markets.